Strain induced irreversible critical current degradation in highly dense Bi-2212 round wire. (30th April 2015) - Bjoerstad, R; Scheuerlein, C; Rikel, M O; Ballarino, A; Bottura, L; Jiang, J; Matras, M; Sugano, M; Hudspeth, J; Di Michiel, M
Abstract: The strain induced critical current degradation of overpressure processed straight Bi-2212/Ag wires has been studied at 77 K in self-field. For the first time superconducting properties, lattice distortions, composite wire stress and strain have been measured simultaneously in a high energy synchrotron beamline. A permanent I c degradation of 5% occurs when the wire strain exceeds 0.60%. At a wire strain of about 0.65% a drastic n-value and I c reduction occur, and the composite stress and the Bi-2212 lattice parameter reach a plateau, indicating Bi-2212 filament fracturing. The x-ray diffraction measurements show that Bi-2212 exhibits linear elastic behaviour up to the irreversible strain limit.